Determinación de la glicemia y riesgo de diabetes en pobladores de ambos sexos de la iglesia adventista, que acuden a la campaña de salud en el centro histórico de Trujillo, mayo - 2012” - Valderrama Cárdenas, Patricia de Lourdes (2012)
In this paper discloses the results of the determination of glucose and risk of diabetes on 75 adults of both sexes of the Adventist Church, attending health campaign in the historiography of Trujillo Center, May - 2012 , between the ages of 18-75 years, which were taken to the respective blood samples and were subjected to analysis by the glucose oxidase enzymatic method thus determining the individual patient whose blood glucose levels normal ranges between 70 to 110 mg / dl . Our aim was to determine the frequency of people with impaired glycemic values, normal and abnormal. For the interpretation of results was used to calculate percentage by division by sex and age, and as glucose: hypoglycemia, normoglycemia and hyperglycemia. The results show that 73.3% presented normoglycemia, 8% presented Hypoglycemia, Hyperglycemia present 18.6%. Of the total 6.7% of women are below the limit, 58.7% are within the normal range and 9.3% have a high glycemic, while 1.3% of men have hypoglycemia, 17.3% showed normoglycemia and 6.7% presented hyperglycemia. By age, the highest percentage of women was constituted hypoglycemia in patients whose ages ranged between the ages of 32-44 years and 45-58 years. It can be concluded that most of the research population keeps your blood sugar levels within normal